Considerations on the state of Ireland, an address delivered at the opening of the seventeenth session - Ingram, John Kells (Statistical and Social Inquiry Society of Ireland, 1864)
Called by the desire of your Council to address you at the opening of a new session, and thus led to consider more closely the condition of Ireland, I could not but be impressed by the grave character of the crisis. When the task was proposed to me, the country was still labouring under the severest pressure she had experienced since 1847. The gloom has now, indeed, in a great measure dispersed, and we see before us, a brightening prospect. But the recollection of those recent trials, and the idea of their possible reoccurance, must still strongly impress every thoughtful mind, I have felt that, at such a time, I could not seek to engage your attention with any mere generalities of social science. It seemed to me that I should best imitate the antecedents of the Society, and best reflect the earnest character of its discussions, if I addressed myself to some of the important questions arising out of the condition of the country. I proceed, therefore, to lay before you a few plain and practical considerations on the present economic circumstances of Ireland, and the measures which appear necessary to ensure her future prosperity.
Read Wednesday, November 18th, 1863
Keywords: Economic conditions; Standards of living; 314.15